2005
DOI: 10.1016/j.ophtha.2005.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Retinal Imaging with High-Speed Ultrahigh-Resolution Optical Coherence Tomography

Abstract: Three-dimensional OCT imaging can be performed using high-speed ultrahigh-resolution OCT. Three-dimensional OCT provides comprehensive visualization and mapping of retinal microstructures. The high data acquisition speeds enable high-density data sets with large numbers of transverse positions on the retina, which reduces the possibility of missing focal pathologies. In addition to providing image information such as OCT cross-sectional images, OCT fundus images, and 3D rendering, quantitative measurement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
387
1
9

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 592 publications
(402 citation statements)
references
References 40 publications
5
387
1
9
Order By: Relevance
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
“…It also is possible to acquire 3-dimensional OCT data that achieve comprehensive retinal coverage and enable individual OCT images to be registered precisely to fundus features. 33 The purpose of this study is to assess the potential of these recent developments to improve the visualization of retinal pathology relative to standard clinical examination and standardresolution StratusOCT. The research prototype OCT instrument developed by our group combines UHR OCT with high-speed detection techniques.…”
mentioning
confidence: 99%
“…7 Recently introduced spectral domain OCT (SD-OCT) measures the interferometric signal detected as a function of optical frequencies, allowing for imaging speeds 50 times faster than TD-OCT, and providing a greater number of images per unit area. [8][9][10][11][12] This increase in resolution and scanning speed allows highdensity raster scanning of retinal tissue while minimizing eye motion artefacts. A better repeatability of measurement compared with Stratus OCT has been reported for spectral domain OCT in healthy eyes.…”
Section: Introductionmentioning
confidence: 99%
“…A dense raster pattern with multiple consecutive B scan at high speed allow for comprehensive retinal coverage. It is possible to acquire complete three-dimensional (3D) data in a time comparable to that of standard OCT protocols that acquire several individual images (Wojtkowski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is helpful for detecting structural changes in retinal diseases or future clinical application, such as planning ERM surgery (Wojtkowski et al, 2005). Rendering also enables different parts of the retina to be made transparent or moved virtually, providing additional morphologic information (Keane and Sadda, 2008).…”
Section: Introductionmentioning
confidence: 99%